INQUIRY BASED LEARNING IN IMPROVING RESULTS STUDENT LEARNING - Ida Royani (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Human life only contains the learning process, learning that begins with a breath and ends with a sigh, meaning that as long as a human is alive, he will continue to learn. At the elementary school education level, there are still many who make teachers as subjects of study so that they do not train children's thinking skills. Not a few teachers still use conventional methods even though the material and learning objectives to be achieved are different. Especially in learning mathematics which is usually the teacher using the lecture method. In this article, it can be used as a reference material in using the mathematics learning model, namely the inquiry learning model or inquiry-based learning. The strategy in the subject approach to student activities is maximally to seek and find, meaning that the inquiry approach places students as learning. All activities carried out are directed at finding and finding out for themselves from something in question, so that it is expected to foster an attitude of confidence which means that in the inquiry approach the teacher is placed not as a learning resource, but as a facilitator and motivator of student learning. The purpose of using inquiry learning strategies is to develop intellectual abilities as part of the mental process.